STUDI FENOMENOLOGI PENGGUNA APLIKASI JAKI DALAM MENGAKSES INFORMASI DAN PELAYANAN PUBLIK - Maha Bunga Dewan Vutri (2021)
Starting from the presence of a JAKI Application which is a new application owned by the DKI Jakarta government. The emergence of these applications, brought changes in public service activities and the reception of information. Activities that were previously carried out offline have now become online. This change creates its own experience for its users. This is what is interesting for the author, therefore this study aims to reveal user experience, as well as user views on the application. The author conducted research with qualitative methods and phenomenological approaches.. The author conducted in-depth interviews with ten people in approximately three months, regarding the experiences of users of the JAKI application in accessing information and public services. From the results of the study, it was found that there were themes related to their experiences when using the JAKI application, namely: 1) Easier, 2) Clear Information, 3) Non-Technical Barriers, 4) Positive Feedback, 5) Uncertain Usage Duration, and 6) Limited Interaction. This research also answers that the meaning of the JAKI application for its users is an innovation and facilities that they can use to facilitate and meet the needs of users to obtain information and public services.